MINAT PEMBELIAN KAIN JUMPUTAN TERHADAP KAIN SONGKET KHAS PALEMBANG (STUDI KASUS: MASYARAKAT KOTA PALEMBANG) - Meriyati, Meriyati; Salim, Amir; Sahroni, Abdullah (Islamic Economics Program, Faculty of Islamic Economics and Business, 2019)
In the millenial era, coincided with the Millennial Road Safety Festival that took place in Ampera bridge of Palembang and attended by the Presiden of Republic of Indonesia, Joko Widodo, a new entry in the Indonesian Record Museum (MURI) is made. The new entrydocumented the longest jumputan cloth in Indonesia that is 1,117 meter long and consisting of 500 designs. In comparison, there is also Songket in Palembang that have been famous since a long time and became the icon of the city that is put on with a sense of pride by its people,but less marketable. The potential and buying power of the public for Palembang songket tend to declinedue to its high price, so that only the upper middle class society who have the capacity to buy this traditional cloth. In addition, songket is used only on formal occasions, thus the lower mid-level people have less purpose to own it. As an alternative of formal attire, Palembangnese uses jumputan that is available in variety of design and less expensive. Its more affordable price make it more popular for the lower mid-level public to buy. Therefore, the authors are interested to analyze about the Comparison of Interest in Purchasing Jumputan Cloth and Palembang Songket in the Market of Palembang City